The fanatical ISIS through the lens of Islamic Law - Uddin, Ahm Ershad (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
Series of attacks under the disguise of Islam; ISIS created an outrage throughout the world, bombings in a number of places, beheading innocent citizens, kidnapping women and children of different sects of Muslims for the cause of harassment and assault, also, burning non-Muslims alive and drowning, then upload those video clips of murder-inaction in the name of the so-called revival of Khilafah and post Quranic verses has raised questions like is conflict one of the principles of Islam? During and after the propagation of Islam did the prophet Muhammad (s.a.w.) ever behead a non-Muslim and present it to a ruler in order to accept Islam? Does Islam allow to amputate any human body who claims the prophet a liar or who talks against him? Furthermore, it is concluded that ISIS misinterprets the fundamentals of Islam and misrepresents them to the world either go against Islam or form the ideal of massacre. This paper intends to comprehend the fanaticism and radical terrorists’ frequent murders of ISIS that is statistically increasing daily, its brutality and more importantly creating a phobia of Islam with their bestial activities, critically, if Islam allows it and how it objectifies this in the light of Islamic law. As well as to lay out a content of Islam as religion and where it stands today under shari'ah.